Totalitarianism and Identity Crisis in a Dystopian Context: Case Study: Veronica Roth’s Divergent (2011) - Cherifi, Fatima Zohra; Afkir, Mohammad (University of Ammar Theledji -Laghouat, 2020)
Identity crisis is one of the problems that affect humans in the phase of adolescents. It is a depicted theme in young adult and dystopian fiction. This study aims at examining the totalitarian regime and the theme of identity crisis in a dystopian context framing Veronica's Roth's novel Divergent (2011) as a case study. It attempts to clarify how totalitarianism is portrayed in the novel relaying on a set of characteristics established by previous authors of dystopian fiction. It also seeks to explore the theme of identity crisis based on what Erik Erickson had suggested in his theory “Stages of Psychological Development”. Moreover, the analysis of the main character's journey of self-quest in the novel paves the way to examine the impact of totalitarian ideology, propaganda and surveillance on Triss's identity crisis. Therefore, this study follows the psychoanalytical approach which seems appropriate to conduct such study. Finally, the study concludes that Triss's identity is a consequence of living under the rule of a totalitarian regime and not a result of her divergence